Concrete-Filled Steel Tube Arch Bridges in China. (February 2018) - Zheng, Jielian; Wang, Jianjun
Abstract: In the past 20 years, great progress has been achieved in China in the construction of concrete-filled steel tube (CFST) arch bridges and concrete arch bridges with a CFST skeleton. The span of these bridges has been increasing rapidly, which is rare in the history of bridge development. The large-scale construction of expressways and high-speed railways demands the development of long-span arch bridges, and advances in design and construction techniques have made it possible to construct such bridges. In the present study, the current status, development, and major innovative technologies of CFST arch bridges and concrete arch bridges with a CFST skeleton in China are elaborated. This paper covers the key construction technologies of CFST arch bridges, such as the design, manufacture, and installation of steel tube arch trusses, the preparation and pouring of in-tube concrete, and the construction of the world's longest CFST arch bridge—the First Hejiang Yangtze River Bridge. The main construction technologies of reinforced concrete arch bridges are also presented, which include cable-stayed fastening-hanging cantilever assembly, adjusting the load by means of stay cables, surrounding the concrete for arch rib pouring, and so forth. In addition, the construction of two CFST skeleton concrete arch bridges—the Guangxi Yongning Yong River Bridge and the Yunnan–Guangxi Railway Nanpan River Bridge—is discussed. CFST arch bridges in China have already gained a world-leading position; with the continuous innovation of key technologies, China will become the new leader in promoting the development of arch bridges.